Manifestation of the Galah Asin Game as a Cultural Heritage to Strengthen the Character of the Nation's Next Generation - Anggriawan, Kevlin; Suhendar, Aris (Pancasila and Civics Education Journal, 2024)
The Galah Asin game is a traditional game that is often played by 10 year old children. This salty pole game is a game that until now has rarely been seen played by children in the current adult era. The Galah Asin game itself actually holds a variety of benefits, because in this game a child is required to work together and socialize with friends around him and this is part of the Indonesian culture which prioritizes togetherness rather than the individual. His presence game online In the current adult era, children are fascinated by its presence so that they forget about the traditional games that exist in the surrounding environment and nowadays we see that the traditional game of galah asin is rarely played by children. This research is aimed at re-existing the traditional galah asin game which is a cultural heritage, so that its presence must not be forgotten and must be preserved from generation to generation. This type of research uses literature study so that the author will explain comprehensively the game of galah asin game. The expected result of this research is that the younger generation will be aware of the importance of making our cultural heritage games available to children, so that galah asin can become a game that is popular with children and defeats the existence of its presence.game online at this time. Keyword: Games, Culture, Galah Asin